Description of Cystodiscus elachistocleis sp. nov. (Cnidaria: Myxosporea) parasitizing the gallbladder of Elachistocleis cesarii from Brazil, based on morphological and molecular analyses - Vieira, Diego Henrique Mirandola Dias [UNESP] (2021)
Numerous pseudoplasmodia containing myxospores belonging to the genus Cystodiscus were found in the gallbladder of Elachistocleis cesarii from Mato Grosso State, Brazil. Herein, we describe Cystodiscus elachistocleis sp. nov., using morphological and small subunit ribosomal DNA sequences. The mature myxospores were ellipsoid to ovoid, measuring in average 10.6 (9.8–11.2) μm in length and 6.2 (5.6–6.6) μm in width. Polar capsules were pyriform and equal in size measuring in average 3.6 (2.8–4.3) μm in length and 2.6 (2.2–3.1) μm in width. Polar filaments had 2–4 coils. The myxospores had 3–5 transverse ridges. The phylogenetic analysis showed Cystodiscus elachistocleis sp. nov. as a sister species of Cystodiscus cf. immersus 1, in a subclade formed by species that parasitize the amphibians gallbladder. This is the first species of Cystodiscus described parasitizing a species of Elachistocleis and the third species of Cystodiscus described in Brazil.